The Effect of The Tragist And Biggs Model on A Cquiring Geographical Concepts For The Fifth Literary Students of The Fifth Grade (Journal of the College of Basic Education, 2025)
The research aims to know the effect of the Tragist and Biggs models in acquiring geographical concepts for students of the fifth literary grade in the secondary day schools for boys in the city of Baghdad. The researcher chose Yemen High school as his research sample and division (A) represented the first expresented the first experimental group and was taught according to the tragist model. (B)The second experimental group is taught according to the biggs model, and division (C) represents the control group and is taught according to the traditional method as for the research tool (the test of acquiring geographical concepts) of the type of multiple choice, then its validity (virtual and content)and the strength of its distinction and the coefficient of difficulty and effectiveness were verified. Wrong alternatives, then proved, and applied after the completion of the experiment, the test for acquiring geographical concepts. The following results were shown: the studeints of the firist and seciond groups turned to the students of the control group the studied according to the traditional method in the test of acquiring geographical concepts. In light of the results, the researcher recommends the teachers of geography to employ modern models in teaching geography and a model cinema tragist and Biggs